Fate and Toxicity of Abamectin in Exposed Fish - Thanomsit, Chutima; Ocharoen, Yhardpeth (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
Abstract Abamectin is one of the worldwide applied insecticides generally known in many trade names such as A.G.BA, Dimatin, Agrotin, Abama, and Jacket. It occurs in fermentation process of soil bacterium; Streptomyces avermitilis, which produce avermectin B1a and avermectin B1b. These substances have the same physical and toxic properties but avermectin B1a shows higher insecticidal property. Thus, most insecticide in this family composes of at least 80% avermectin B1a. Because of its high toxicity, it is applied in quite few amounts. It is classified as contact and semi-systemic insecticide thus it can control most insects such as thrips, lime butterfly, and rice leaffolder. However, it could be released and contaminated into the waters by both intently and non-intently. Many researches showed its harmful effects on aquatic environment especially freshwater fish; for example, histology changes in many organs and degenerative changes in brain, gill and kidney. Based on above information, the study on structure, mode of action, and toxicity of abamectin is required.